Pengembangan Desa Wisata Batik Girilayu di Desa Girilayu Berbasis Local Wisdom Menuju Global Market - suherlan, Yayan; Wida Riptanti, Erlyna; Widyamurti, Nidyah (Warta LPM, 2023)
Since 2020, the Karanganyar Regency Government has proclaimed Girilayu Village as a tourist village and the Giriarum Batik MSMEs have produced batik tulis products that are the pride of the community. The existing problems are related: tourism village branding and Girilayu-style batik products have not been identified; the tourism village management program and its unique products already exist, but have not been carried out massively and integrated; Batik Giriarum MSMEs batik tulis products already have a clear market segmentation, but digital marketing and information technology have not been fully utilized. BUMDes, Pokdarwis, Girilayu Village Government, and MSMEs Batik Giriarum are aware of the existing problems and their solutions but have not been able to implement the program properly. This community service aims to: 1) Increase understanding of branding, information technology, and digital marketing; 2) Improve skills and knowledge about the management of tourist villages and their unique products; and 3) Improve local potential management capacity. The method used to achieve the goal are participatory-based community service activities involving all stakeholders in the planning and implementation. Activities are designed and implemented in a comprehensive and integrated manner as a solution to problems so that the Village Government, BUMDes, Pokdarwis, and the Batik Giriarum MSMEs are motivated and concerned about their role as agents of change for the development of the Girilayu Tourism Village. The results of the activity showed a significant increase in the batik-making community and the management of the Girilayu Tourism Village, including: 1) Giriarum Batik MSMEs understand and contribute to the design of the brand identity of the Girilayu Batik Tourism Village; 2) BUMDes and Pokdarwis HR insights and skills in managing local potential are growing; and 3) Active promotion of MSMEs Batik Giriarum batik products and tourist villages through social media.